Peer-led intervention for individuals with major depression: study protocol for a randomized controlled trial (SUPEERMood) - Xandra Gonzalez-Garcia; M. Lucia Moreno-Sancho; Patricia Roa-Díez; Yolanda Caceres-Tejeiro; Sarah-Louise Auvergne Flowers; Concha Gómez de Montes; Miquel Bennasar-Veny; Mauro García-Toro; Aina M. Yañez (BMC Psychiatry, 2024)
Abstract Background Major Depressive Disorder (MDD) is one of the most disabling mental health problems worldwide. The Recovery Model emphasizes peer support to empower individuals with MDD, improve self-management, and patients' quality of life. Despite the demonstrated efficacy of peer-led interventions, further research is needed due to methodological limitations and variability in interventions across studies. Therefore, the objective of this trial is to evaluate the effectiveness of an adjuvant peer-led intervention for the reduction of depressive symptoms in individuals diagnosed with MDD attended in primary care mental health units. Methods A controlled, parallel, randomized clinical trial will be conducted. The intervention group (n = 35) will receive 6 weeks of peer-led sessions based on a peer support program drive whilst supervised by nurses, while the control group (n = 35) will use a mobile Health (mHealth) application for emotional wellness based on CBT for 6 weeks. Measurements will be collected at baseline, at 6 weeks, at 6 and 12 months after the intervention to evaluate post-intervention effects. The primary outcome is the reduction of depressive symptoms through the Beck Depression Inventory (BDI-II) after the intervention. Secondary outcomes will involve measures such as adherence to psychiatric treatment, quality of life, adherence to mediterranean diet, alcohol consumption and physical activity. Discussion We hypothesize that this peer-led intervention, in contrast to the mHealth, will show improvement in BDI-II score reduction of 6 points after six weeks, 6 and 12 months. Standardized peer-led programs can benefit patients and professionals in terms of efficacy and feasibility of clinical treatment of depression, healthy habits, self-care and quality of life. In addition, they can provide recovery and relapse reduction, improved psychosocial support, minimization of intensive care use, and support for patient autonomy through self-management. Trial registration The trial protocol is prospectively registered with ClinicalTrials.gov under protocol registration number NCT06398561. Date of registration: May 01, 2024. Recruitment is ongoing.